MOLECULAR DOCKING, 3D-QSAR AND DE NOVO DESIGN OF BENZIMIDAZOLES AND IMIDAZOLINES (S)-ISOTHIAZOLIDINONES DERIVATIVES AS PTP 1B INHIBITORS - GRANADOS R., Judith C.; ARIAS P., Elsa R.; PACHECO L., Dency J.; VALDIRIS A., Verónica; VIVAS-REYES, Ricardo (Vitae, 2010)
A study of the relationship-dimensional quantitative structure (3D-QSAR) with 40 molecules derived from benzimidazole and imidazoline (s)-isotiazolidinonas and their union with the active site of Protein Tyrosine Phosphatase 1B using the program GOLD 3.0 was carried out. The molecular supression of the ligands in the grid was performed by the Database Alignment method. The best model formed by combining the esteric field and electrostatic fields of CoMFA, yielded the following parameters: q2 = 0.659 and r2 = 0.997. Using LeapFrog module of Sybyl was possible to generate more than 10,000 new molecules of which 46 showed theoretically a better value of biological activity than their forerunner. The data generated by this study could promote the design of new and more potent PTP 1B inhibitors as agents for the treatment of diabetes.